Genetic variability, correlation and path analysis in wheat - Nukasani, Vamshikrishna; Potdukhe, Nilkanth Ramchandra; Bharad, Swati; Deshmukh, Shradha; Shinde, Sachin Murlidhar (Journal of Cereal Research, 2013)
Hundred fourteen pre-breeding lines of wheat were evaluated for variability. High values of GCV and PCVwere recorded for tillers meter-1 and grain yield meter-1, whereas moderate values for rest of the traits. Highheritability coupled with high genetic advance were recorded for traits plant height, tillers m-1, grain yield m-1,grain wt spike-1 and spike length indicating that these characters are governed by additive gene effects anddirectional selection for these traits would be more effective. Correlation and path analysis studies revealed that,three characters, tiller number m-1 >grain weight spike-1 >number of grains spike-1 in that order are the mostimportant characters as these exhibited positive and strong association and maximum positive direct effects ongrain yield. Therefore while imparting the selection in wheat characters tiller number m-1, grain weight spike-1and number of grains spike-1 must be given preference.